ptf1a+, ela3l− cells are developmentally maintained progenitors for exocrine regeneration following extreme loss of acinar cells in zebrafish larvae - Nicole Schmitner; Kenji Kohno; Dirk Meyer (The Company of Biologists, 2017)
The exocrine pancreas displays a significant capacity for regeneration and renewal. In humans and mammalian model systems, the partial loss of exocrine tissue, such as after acute pancreatitis or partial pancreatectomy induces rapid recovery via expansion of surviving acinar cells. In mouse it was further found that an almost complete removal of acinar cells initiates regeneration from a currently not well-defined progenitor pool. Here, we used the zebrafish as an alternative model to study cellular mechanisms of exocrine regeneration following an almost complete removal of acinar cells. We introduced and validated two novel transgenic approaches for genetically encoded conditional cell ablation in the zebrafish, either by caspase-8-induced apoptosis or by rendering cells sensitive to diphtheria toxin. By using the ela3l promoter for exocrine-specific expression, we show that both approaches allowed cell-type-specific removal of >95% of acinar tissue in larval and adult zebrafish without causing any signs of unspecific side effects. We find that zebrafish larvae are able to recover from a virtually complete acinar tissue ablation within 2 weeks. Using short-term lineage-tracing experiments and EdU incorporation assays, we exclude duct-associated Notch-responsive cells as the source of regeneration. Rather, a rare population of slowly dividing ela3l-negative cells expressing ptf1a and CPA was identified as the origin of the newly forming exocrine cells. Cells are actively maintained, as revealed by a constant number of these cells at different larval stages and after repeated cell ablation. These cells establish ela3l expression about 4-6 days after ablation without signs of increased proliferation in between. With onset of ela3l expression, cells initiate rapid proliferation, leading to fast expansion of the ela3l-positive population. Finally, we show that this proliferation is blocked by overexpression of the Wnt-signaling antagonist dkk1b. In conclusion, we show a conserved requirement for Wnt signaling in exocrine tissue expansion and reveal a potential novel progenitor or stem cell population as a source for exocrine neogenesis after complete loss of acinar cells.